Recent advances in delay cell VCOs [application notes] - Moghavvemi, M.; Attaran, A. (IEEE, 2011)

(untitled)
Voltage-controlled-oscillators (VCOs) are the heart of every wired and wireless communication system, including phase-lock-loop (PLL), clock-data-recovery (CDR), serial-link-radio, digitalmillimeter-radar (DMR) [1], CPUs, and microprocessorbased systems [2] [3]. Low phase noise and wideband frequency coverage are two of the most crucial issues in VCO design(s) [4]. Monolithic VCOs have two main topologies: the ring VCO and inductance (L) and capacitance (C) VCO. Ring structures provide a wide tuning range, inferior phase noise performance (because of their low quality factor), smaller layout area, lower dissipated power, and less design complexity compared to LC structures [5].